Nanomaterials in Liquid Crystals - Ingo Dierking (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The dispersion of nanomaterials in liquid crystals, both of the thermotropic and the lyotropic kind, has attracted much interest over recent years. This is in part related to the success of liquid crystals in several applications, in particular flat screen displays, besides others. The dispersion of nanoparticles allows the fine-tuning of liquid crystalline properties and the addition of functionalities associated with the properties of the nanoparticles. These include the addition of ferroelectricity, magnetic properties, optic and plasmonic properties, for example through quantum dots and gold nanoparticles, but also directed conductivity, by exploiting the respective conductivity anisotropy of nanotubes. In addition, such behaviors can be achieved through transfer and templating of the self-organization of the liquid crystalline order onto dispersed anisotropic nanoparticles, allowing the formation of ordered nanostructures. Furthermore, the formation of partially ordered fluids can be induced by dispersing shape anisotropic nanoparticles in an isotropic solvent. Such lyotropic systems have recently experienced a revived interest. This genuinely multidisciplinary field of research has led to a wealth of novel systems in soft condensed matter and promises new applications in the areas of displays, optical elements, meta-materials, sensors, drug delivery, and many more. Various examples are presented in this publication.